Dryopteris Plant Extracts as a Green Inhibitor for the Corrosion Inhibition of Mild Steel in Acidic Media - Niroula, Ramala; Niroula, Sudiksha; Pokhrel, Dilli Ram (Damak Campus Journal, 2024)
The corrosion inhibitive properties of Dryopteris wallichiana leaves extract was investigated for mild steel in different concentration of acidic medium of HCl. This study revealed that the corrosion rate increases with the increase in acid concentration whereas the corrosion rate decreases with the increase in inhibitor concentration. It is associated with the action of corrosive medium with the metal sample(MS) and the active phytochemicals constituent present in the inhibitor. The maximum inhibition efficiency was found to be 85.84% and the maximum corrosion rate was found to be 214.8gm m-2hr-1 in 2M HCl.